Optimising carbon capture and solids recovery using seawater reverse osmosis desalination brine - Oo, Guoxuan (Nanyang Technological University, 2024)
There is an urgent need to reduce carbon emissions globally to curb the worsening climate change. It is also important to cause minimal disruption to current processes in the short term to limit job loss. Concurrently, there is also a need to address the increasing volume of desalination brine that has an adverse impact on the environment due to its high salinity. The potential solution to both problems is carbon capture using desalination brine. The focus of this paper is on pretreatment of brine for chlor-alkali process. This paper found the optimal final pH for sequential addition of NaOH and bubbling of CO2 to be 12.5 and 11.5, respectively. At these pH values, the formation of calcium carbonate was maximised, maximising the carbon capture aspect of brine pretreatment, resulting in near 100% Ca and Mg removal. Optimal pH of alternative alkali for pretreatment of brine at 25°C were also identified: pH 10.5 for sodium carbonate, corresponding to 95% Ca and 75% Mg removal; and pH 7.9 for sodium bicarbonate, corresponding to 97% Ca and 38% Mg removal. These parameters serve as a guide for system design for large scale desalination brine treatment and carbon capture system.